2020
DOI: 10.1124/jpet.119.263509
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and Function of Prostaglandin E2Receptors in Mouse Uterus: Translational Value for Human Reproduction

Abstract: In vitro fertilisation (IVF) Prostaglandin (PG) Section assignment: Drug Discovery and Translational Medicine This article has not been copyedited and formatted. The final version may differ from this version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…For example, previous experiments have discovered that 15-methyl PGE2, or 16, 16-dimethyl PGE2 are more stable than PGE2 when administered intravenously, orally and intrajejunal 196 - 198 . Besides, PGE2 analogs have been widely used in clinical practice for cervical ripening and labor induction 199 . Another strategy available is the incorporation of engineered biomatrices for PGE2 control release by different approaches, such as encapsulation and chemical bonding ( Figure 7 C ).…”
Section: Pge2-based Therapeutic Strategies For Tissue Regenerationmentioning
confidence: 99%
“…For example, previous experiments have discovered that 15-methyl PGE2, or 16, 16-dimethyl PGE2 are more stable than PGE2 when administered intravenously, orally and intrajejunal 196 - 198 . Besides, PGE2 analogs have been widely used in clinical practice for cervical ripening and labor induction 199 . Another strategy available is the incorporation of engineered biomatrices for PGE2 control release by different approaches, such as encapsulation and chemical bonding ( Figure 7 C ).…”
Section: Pge2-based Therapeutic Strategies For Tissue Regenerationmentioning
confidence: 99%
“…Increase of PGE-EP2 transmembrane receptors in the plasma of ASD patients of course is concomitant with high rate of brain EP2 receptors deletion which from the theoretical point of view could decrease the pro-inflammatory effects of PGE2. Excitingly, the neuroprotection of PGE2-EP2 has been documented only recently, while a distinction among PGE2 receptors had not been made previously [ 31 , 32 ]. Interestingly, Wu et al and others reported that EP1 and EP3 receptor signaling has inflammatory affects in vitro and in vivo models of Cerebral hypoperfusion, or inadequate blood flow in the brain [ 33 36 ], as a well-known disorder in most ASD patients [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on heart failure in female mice are limited. With respect to PGE2 specifically, studies are generally confined to the effects of PGE2 in pregnancy, [31][32][33] peripartum/postpartum cardiomyopathy, 34,35 and cardiac arrest. 36 To our knowledge, no 1 has investigated the effect of PGE2 on cardiac contractility in female mice.…”
Section: Discussionmentioning
confidence: 99%